Kewenangan Penyelesaian Sengketa Ekonomi Syari’ah pada Perbankan Syari’ah di Samarinda - Hervina Hervina (FENOMENA, 2014)
To anticipate the legal dispute about syariah economyin society, syariah banks or non-banks as well as the other users, they should realize that they could not depend on the courts if syariah principles wants to be existed. It is because the basic principles of the cases are really different. The changing of UU Nomor 7 Tahun 1989 about Religious Court (UUPA)  becomes UU No. 3 Tahun 2006 and No. 50 Tahun 2009 is a legislacy product which firmly gives the religious courts competency to bring the lawsuits of syariah econonmy to the courts. Then, UU Nomor 21 Tahun 2008 about Syariah banking (UUPS) was coused to be effective to strengthen the religious courts competency to handlethe lawsuits of syariah economy, particularly syariah banking. Based on the UUPA and UUPS, the religious courts should have an absolute competency to bring the lawsuits of syariah econonmy. In fact, the justification of the religious courts competency is still debatable.